Comparison in terms of material quantity between non-seismic and seismic design for selected buildings in Malaysia - Farhanah Faisal; Shaharudin Shah Zaini; Moustafa Moufid Kassem; Mohd Irwan Adiyanto (Penerbit Universiti Kebangsaan Malaysia, 2024)
Almost all buildings in Malaysia were previously designed for non-seismic loading. As such, the need to consider seismic load poses challenges for the engineers and project owners. In order to enlighten the stakeholders on the effect of adopting seismic design, the impact on building material cost and quantities must be investigated in advance. Although many studies have been conducted, the use of hypothetical building models and not considering the actual soil factors in Malaysia may yield unrealistic results. As such, this study is conducted with the aim to evaluate the change in the material quantities of the main frame members using six existing building models subjected to peak ground acceleration of 0.16g and situated on soil type D. The analysis, design and taking-off were conducted with the aid of Tekla Structural Designer software. The results showed significant increase in terms of the material quantity required for the main frame members when seismic design was considered. The increase in the concrete volume and reinforcement tonnage was calculated to be in the range of 6.92% to 404.86% and 3.23% to 563.94%, respectively. The development of high base shear force, the amplification of the seismic force by the soft soil, and relatively stringent detailing in DCM were identified as the contributing factors. With a broader spectrum of results, the stakeholder can anticipate the increase in the material cost for adopting seismic design that can be useful for design submission and project cost estimation.